Influence of Partially Substituting Wheat Flour with Tiger Nut Flour on the Physical Properties, Sensory Quality, and Consumer Acceptance of Tea, Sugar, and Butter Bread - Nazir Kizzie-Hayford; Joshua Akanson; Jerry Ampofo-Asiama; Ernest Ekow Abano (International Journal of Food Science)
Tiger nut is a valuable source of fiber, lipids, minerals, and carbohydrates. However, avenues for incorporating tiger nuts into food remain underexplored, especially in several tropical countries where the plant grows well. The current study investigated the effects of partially substituting wheat flour (WF) with tiger nut flour (TNF) on the physical and sensory properties of different bread types to evaluate the more amenable system for tiger nut incorporation. The substitution was done at WF:TNF ratio of 100 : 0, 90 : 10, 85 : 15, 80 : 20, 75 : 25, and 70 : 30 for butter bread (Bb), tea bread (Tb), and sugar bread (Sb). The results show that WF substitution with TNF increased bread brownness and color saturation and decreased lightness, showing the highest impact on Sb, followed by Tb and Bb. Additionally, bread-specific volume decreased significantly after 20% (Bb), 25% (Tb), and 30% (Sb) TNF substitution. Furthermore, substituting WF with 30% TNF increased crumb hardness from approx. 1.87 N to 3.64 N (Bb), 3.46 N to 8.14 N (Tb), and 6.71 N to 11.39 N (Sb) and caused significant increases to 17.80 N (Tb) and 21.08 N (Sb) after 3 d storage. Only a marginal effect on storage hardness (4.32 N) was observed for Bb. Substituting WF with 10% TNF for Bb or 25% TNF for Tb led to significantly higher consumer (N=56) scores for all attributes and overall acceptability. However, no significant effect on the overall acceptability of Sb was observed. Flash profiling showed frequently used descriptors for Bb as firm, moist, buttery, smooth, and astringent. After 10% TNF substitution, descriptors were chewy, firm, sweet, porous, dry, and caramel, and that of 30% TNF were grainy, chocolate, brown, nutty, and flaky. Substituting WF with TNF increased the lipids, fiber, and minerals content but decreased the protein and carbohydrate contents of bread. TNF substitution led to different physical and sensory effects depending on bread type, showing that Bb with 10% or Tb with 25% TNF is more comparable with the overall acceptance quality of 100% WF. The study is relevant for utilizing tiger nuts as an ingredient in bread products.